SPECTROPHOTOMETRIC METHOD FOR DETERMINING THE ASSAY OF HESPERIDIN IN THE COMPOSITION OF POLYMER COMPOSITE MATERIAL OBTAINED BY CENTRIFUGAL FIBER FORMATION - LISOVYI, VADYM; BESSARABOV, VOLODYMYR; GOY, ANDRIY; KOSTIUK, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
A spectrophotometric method for the assay of the bioflavonoid hesperidin in polymer composite materials, namely in solid dispersed systems obtained by the method of centrifugal fiber formation, has been developed. The proposed method is based on the qualitative reaction of hesperidin with ferric (III) chloride, resulting in the formation of a green compound with a maximum optical absorption at a wavelength of 602 nm. The validation characteristics of the developed method, in particular, linearity, precision, specificity, and stability, were investigated. The validation of the proposed method was carried out in accordance with the requirements of the State Pharmacopoeia of Ukraine (SPU). Spectrophotometric measurements were performed using an OPTIZEN POP UV spectrophotometer (Masys, South Korea) in quartz glass cuvettes with an optical layer thickness of 1 cm (Agilent, USA). In the course of the experimental studies, the wavelength of 602 nm is specific for determining the assay of hesperidin in centrifugally formed solid dispersed systems, which is confirmed by the analysis of the absorption spectra of related substances. It was found that the developed spectrophotometric method for the quantitative determination of hesperidin in polymeric solid dispersed systems using 0.3 n of ferric (III) chloride is linear (R2= 0.997) in the range of hesperidin concentrations of 80-120 %. The confidence interval for the convergence and reproducibility of the analysis does not exceed the maximum permissible limits, which indicates the accuracy of the method. When changing the wavelength by ±2 nm, the standard deviation of the results obtained is 0.12%, which proves the stability of the system. It is proved that all the selected validation characteristics of the spectrophotometric method for the assay of hesperidin in centrifugally formed solid dispersed systems meet the acceptance criteria. We concluded that the proposed methodology is valid.